Intermittently Scanned and Continuous Glucose Monitor Systems: A Systematic Review on Psychological Outcomes in Pediatric Patients - Franceschi, Roberto; Micheli, Francesca; Mozzillo, Enza; Cauvin, Vittoria; Liguori, Alice; Soffiati, Massimo; Giani, Elisa (Frontiers in Pediatrics, 2021)
AIM: To explore the impact of real-time continuous glucose monitoring (rtCGMs) or intermittently scanned/viewed CGM (isCGM) on psychological outcomes in children and caregivers, and to grade the level of evidence. METHOD: Systematic review of the literature from PubMed, Embase, Cochrane Library, Web of Science, CINAHL, Nursing reference center, Up to date, Google Scholar and PsycINFO databases. The studies selected used validated questionnaires for investigating the psychological outcomes. We applied GRADE (Grading of Recommendations Assessment, Development and Evaluation) to rank the quality of a body of evidence. RESULTS: A total of 192 studies were identified in the initial search and after the process of evaluation 25 studies were selected as appropriate to be included in this systematic review. We found in moderate quality studies that isCGM in adolescents can improve diabetes related distress, family conflicts, fear of hypoglycemia and quality of life, while depression, anxiety and quality of sleep have not yet been evaluated by validated questionnaires. In moderate – high quality studies, rtCGM technology does not impact on diabetes burden, diabetes specific family conflict and depressive symptoms. The effect on fear of hypoglycemia, sleep quality and anxiety is still debated and RCT studies powered to find significant results in psychological outcomes are lacking. RtCGM increases satisfaction and quality of life in parents and patients wearing rtCGM. CONCLUSION: these data present an interesting point to consider when families are deciding whether or not to start CGM use, choosing between rtCGM to reach a tighter metabolic control, or isCGM which allows greater benefits on psychological outcomes.